1993
DOI: 10.1002/pd.1970131210
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic carrier of two CFTR mutations: Consequences for prenatal diagnosis?

Abstract: The cystic fibrosis (CF) gene has been observed to have the highest frequency of mutations in the Caucasian population. Prenatal diagnosis can now be performed with a high degree of accuracy since the identification of most of the gene's mutations, as well as the characterization of intragenic markers. However, the observation of a distribution of clinical phenotypes increases the need to identify a mild phenotype and avoid false-negative diagnosis. By screening most of the exons of the CFTR gene, we showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…2A, there was little or no current under basal conditions, and application of CPT-cAMP activated large currents that reversed at the Cl Ϫ equilibrium potential (close to 0 mV with the solutions used). The currents were glibenclamide-sensitive and DIDS-and TS-TMcalix [4]arene-insensitive as expected for CFTR Cl Ϫ current (data not shown). These currents were activated a few seconds after stimulation and were slowly reversible after washout of CPT-cAMP.…”
Section: Processing Of Cftr Mutants-many Cf-associated Mutations Caussupporting
confidence: 70%
See 1 more Smart Citation
“…2A, there was little or no current under basal conditions, and application of CPT-cAMP activated large currents that reversed at the Cl Ϫ equilibrium potential (close to 0 mV with the solutions used). The currents were glibenclamide-sensitive and DIDS-and TS-TMcalix [4]arene-insensitive as expected for CFTR Cl Ϫ current (data not shown). These currents were activated a few seconds after stimulation and were slowly reversible after washout of CPT-cAMP.…”
Section: Processing Of Cftr Mutants-many Cf-associated Mutations Caussupporting
confidence: 70%
“…The number of complex CFTR genotypes identified, including double-mutant alleles where two missense mutations are carried by the same chromosome, has been growing (2)(3)(4)(5)(6). It is difficult to evaluate the contribution of each mutation/or polymorphism to the phenotype as mutations in cis may act in concert to alter or reverse defective CFTR function and thus modify the CF phenotype (2).…”
mentioning
confidence: 99%
“…The same seems to apply to the AF508-V1212I allele (Macek et al, 1993). Other in cis missense mutations have been reported, namely F508C-Sl251N (Kalin et al, 1992), G628R-S1235R (Mercier et al, 1995) and R74W-D1270N (Verlingue et al, 1993). The latter was also detected by us in compound heterozygosity with AF508 in a Portuguese patient with a very mild CF phenotype (to be reported elsewhere).…”
Section: Resultsmentioning
confidence: 60%
“…Since the gene and the major mutation responsible for CF (AF508) were identified in 1989 , more than 500 presumed pathogenic mutations and more than 100 DNA normal sequence variations have been identified in the CFTR gene (Newsletter from the CF Genetic Analysis Consortium, March 22, 1995). However, to our knowledge, only five complex alleles containing more than one mutation, mostly missense mutations, have been described in the CFTR gene (Dork et al, 1991, Kalin et al, 1992, Verlingue et al, 1993Macek et al, 1993;Mercier et al, 1995). We describe here another complex CFTR allele containing a missense mutation in exon 7 and a nonsense mutation in exon 19.…”
Section: Introductionmentioning
confidence: 96%
“…Our patients were screened for all exons, from exon 34 to exon 46, even if a causative mutation was identified, in order to localize a possible second nucleotide variation which could have a phenotypic effect on the severity of the disease, as has been the case with other genes (Verlingue et al 1993;Savov et al1995) In this cohort we have identified novel mutations. Most of these mutations are point mutations except those with the insertion of 9 or 23 nucleotides: 5 of them are ins/del or nonsense mutations that are clearly deleterious, 2 are missense mutations, 1 is an in-frame insertion of 3 amino acids and 3 are possible splicing mutations.…”
Section: Discussionmentioning
confidence: 97%